Studies on Host Range and Incidence Level of Cow Horn Bug, Oxyrachis tarandus Fab. in Madhya Pradesh - Garg, Vinod Kumar (Indian Forester, 2015)
Cow horn bug, Oryrachis tarandus Fab. (Homoptera: Membracidae) feeds on a wide range of host plants and cause economical damage. The study documents 65 host plants distributed in 22 families. Maximum incidences were observed in the plant belonging to family Fabaceae (27.69%) trailed by Moraceae and Euphorbiaceae (9.23%), Asteraceae (7.69%), Amarantheaceae (6.15%) , Apocynaceae, Rutaceae, Solanaceae, Malvaceae and Myrtaceae. In excess of 26.15% were observed from fruit crops followed by trees (24.62%), weeds (21.54%), flowers (15.38%), field crops (7.69%). However vegetable, ornamental and aromatic plant (1.54%) have least preferred.